Knowledge, attitudes and practices regarding the prevention of type 2 Diabetes Mellitus among overweight and obese adults in Manzini, Eswatini : a cross-sectional study - Chideme-Chinovhiringa, Karen (Stellenbosch : Stellenbosch University, 2020)
Thesis (MMed)--Stellenbosch University, 2020.